Sustainable Heterogeneous Catalysts for CO2 Utilization by Using Dual Ligand ZnII/CdII Metal–Organic Frameworks. Issue 59 (25th September 2018) - Parmar, Bhavesh; Patel, Parth; Kureshy, Rukhsana I.; Khan, Noor‐ul H.; Suresh, Eringathodi
Abstract: Two‐dimensional Zn II /Cd II ‐based dual ligand metal–organic frameworks (MOFs) [M(CHDC)(L )]⋅ H2 O n involving 4‐pyridyl carboxaldehyde isonicotinoylhydrazone (L ) in combination with flexible 1, 4‐cyclohexanedicarboxylic acid (H2 CHDC) as linkers have been synthesized by adaptable synthetic protocols including a green mechanochemical (grinding) method. Characterization, chemical/thermal stability, phase purity, and solid‐state luminescent properties of both MOFs have been established by various analytical methods. Structural analysis revealed dimeric metal clusters composed of [M2 (CHDC)2 ] n loops doubly pillared with L, generating a 2D framework. Both MOFs can be used as highly active solvent‐free binary catalysts for CO2 cycloaddition with epoxides in the presence of the co‐catalyst tetrabutylammonium bromide (TBAB) with good catalytic conversion in up to six catalytic cycles without significant loss of activity. The present investigation demonstrates the application of MOFs as efficient heterogeneous catalysts for CO2 utilization under moderate reaction conditions. Based on the single‐crystal X‐ray data, a probable mechanism for the cycloaddition reaction has also been proposed. Abstract : Going green : Green, ecofriendly mechanochemical synthesis of Zn II /Cd II ‐based mixed ligand metal–organic frameworks (MOFs) has been utilized as an efficient platform for heterogeneous catalysis of the cycloaddition of CO2 to epoxide at moderate and solvent‐free reaction conditions to give value‐added cyclic carbonates.